Remifentanil Versus Placebo for Analgesia During External Cephalic Version: A Randomized Clinical Trial. Issue 1 (March 2015) - Muñoz, H.; Guerra, S.; Perez-Vaquero, P.; Valero Martinez, C.; Aizpuru, F.; Lopez-Picado, A.
Abstract : ( Int J Obstet Anesth . 2014;23(1):52–57)